The Comparative Evaluation Of Chemical, Chromatographic And Immunological Tests For The Detection Of Mefloquine And Other Antimalarial Drugs In Body Fluids. - Navaratnam, Profesor Madya (Dr.) V.; Payne, Dr. D. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1991)
The third Penang workshop in the TOR sponsored antimalarial drug studies series, entitled "Workshop for the Comparative Evaluation of Chemical, Chromatographic and Immunological Tests for the Detection of Mefloquine and Other Antimalarial Drugs in Body Fluids" - Penang III - was held from 22 to 26 July 1991 at the National Drug Research Centre Universiti Sa;ns Malaysia, Penang, Malaysia.